Bee-bim bop! - Park, Linda Sue.; Lee, Ho Baek (New York : Clarion Books, 2005)
A child, eager for a favorite meal, helps with the shopping, food preparation, and table setting.
Keywords: Cooking, Korean -- Fiction; Koreans -- Fiction; Stories in rhyme